The Effect of the Smartick Indonesia Application on the Ability of Mathematics Literacy Material for Counting Numbers of Students of Class V Minu Durungbedug Candi Sidoarjo - Mustika Yuliya Sari; Rofiqoh Nirwana (Al-Madrasah: Jurnal Ilmiah Pendidikan Madrasah Ibtidaiyah, 2026)
This study is motivated by the urgency to strengthen the numeracy literacy competence of fifth-grade students at MI Nahdlatul Ulama Durungbedug Candi, particularly regarding the topic of whole number operations, which remains suboptimal. This research aims to evaluate the effectiveness of adaptive-based digital media, specifically Smartick Indonesia, as an intervention to accelerate mathematical literacy skills. The investigation was conducted using a quantitative approach with a quasi-experimental method, utilizing a nonequivalent control group design. Research participants involved 48 students distributed into an experimental class (24 students) and a control class (24 students). Data collection was performed using a mathematical literacy test instrument aligned with PISA standards that has been tested for validity. Statistical data processing techniques applied the Independent Sample t-Test and N-Gain calculation supported by SPSS version 24 software. The study findings confirm a tangible positive impact from the utilization of the Smartick application on students' literacy competence, indicated by a significance value (Sig. 2-tailed) of 0.000, which is below the 0.05 threshold. Descriptively, the mean posttest score in the intervention group was recorded at 83.70, surpassing the comparison group, which only reached 66.50. Furthermore, effectiveness analysis revealed that the experimental class achieved an N-Gain index of 0.51, classified in the moderate category, while the control class only reached 0.17, which falls within the low category. This gap demonstrates that the use of the Smartick Indonesia application yielded a more optimal improvement in students' mathematical literacy compared to conventional instruction.